The Return of "One Guideline, One Textbook" Policy: Moral Education Textbook and Teacher Interaction in China - Ye, Wangbei (Comparative education review, 2022)
Since China issued its "one guideline, various versions of textbooks" policy in the mid-1980s, several versions of moral education textbooks have been used in grades 1-9 and more than one version in grades 10-12. Recently, China has attempted to tighten its control over textbooks and reinstate its previous "one guideline, one textbook" policy in three subjects: history, Chinese language, and moral education. This study, based on data collected from interviews, observation, and document analyses involving nine textbook authors, six reviewers, and 27 school teachers, analyzes the complexity and dynamics in textbook-teacher interaction in a controlled context in moral education in China.